Cytotoxic Immunity in Peripheral Nerve Injury and Pain - Davies, Alexander J.; Rinaldi, Simon; Costigan, Michael; Oh, Seog Bae (Frontiers in Neuroscience, 2020)
Cytotoxicity and consequent cell death pathways are a critical component of the immune response to infection, disease or injury. While numerous examples of inflammation causing neuronal sensitisation and pain have been described, there is a growing appreciation of the role of cytotoxic immunity in response to painful nerve injury. In this review we highlight the functions of cytotoxic immune effector cells, focusing in particular on natural killer (NK) cells, and describe the consequent action of these cells in the injured nerve as well as other chronic pain conditions and peripheral neuropathies. We describe how targeted delivery of cytotoxic factors via the immune synapse operates alongside Wallerian degeneration to allow local axon degeneration in the absence of cell death and is well-placed to support the restoration of homeostasis within the nerve. We also summarise the evidence for the expression of endogenous ligands and receptors on injured nerve targets and infiltrating immune cells that facilitate direct neuro-immune interactions, as well as modulation of the surrounding immune milieu. A number of chronic pain and peripheral neuropathies appear comorbid with a loss of function of cellular cytotoxicity suggesting such mechanisms may actually help to resolve neuropathic pain. Thus while the immune response to peripheral nerve injury is a major driver of maladaptive pain, it is simultaneously capable of directing resolution of injury in part through the pathways of cellular cytotoxicity. Our growing knowledge in tuning immune function away from inflammation towards recovery from nerve injury therefore holds promise for interventions aimed at preventing the transition from acute to chronic pain.